Global second order effects in reinforced concrete buildings: simplified criterion based on Galerkin’s method - Rafael Nunes da Cunha; Camila de Sousa Vieira; Rainara Souza Gomes; Ludmila dos Santos da Silva; Ludmilson Abritta Mendes; David Leonardo Nascimento de Figueiredo Amorim (Revista IBRACON de Estruturas e Materiais, 2024)
Abstract Global second order effects in reinforced concrete buildings can be estimated using numerical or simplified methods, such as the γz coefficient, presented in the Brazilian standard. This paper proposes a new simplified parameter, which is deduced by the Galerkin’s Method by Weighted Residuals. In order to evaluate the accuracy of the proposed methodology, 42 planar frames (21 framed system structures and 21 dual system structures) were analysed in terms of internal forces and displacements. Such results were compared to those obtained by the γz coefficient and to the reference results obtained throughout a geometric nonlinear elastic finite element program. The precision of the results was defined by statistical analyses, which showed that the results using the proposed parameter were closer to the reference ones, even in the recommended range for using the γz coefficient.